Efekt zarażania jako mechanizm rozprzestrzeniania się kryzysów walutowych - Korczyńska-Rechul, Aneta (Contagion Effect as a Mechanism of Spreading Currency Crises, 2005)
Cuuency crises of the 1990s gave a new impetus to a debate in academic and policy circles about international transmission of shocks. While originally the literature linked currency crises to countryspecific macroeconomics factors, it has focused more recently on self-fulfilling expectations and contagion effects. This article provides an overview of the literature on contagion. In particular this paper studies channels through which contagion might have spread and highlights factors which make country susceptible to contagion. The channels studied in the paper are spillover effects monsoonal effects and pure contagion. This article focuses in particular on the role of liquidity problems, information asymetries, incentive problems and changes in the rules of the games in propagation of volatility in financial markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 59-70